A theoretical analysis on the intramolecular proton transfer of alpha-alanine in an aqueous medium - Sambrano, JR; de Sousa, A. R.; Queralt, J. J.; Andres, J.; Longo, Elson [UNESP] (Elsevier B.V., 1998)
Intramolecular proton transfer from oxygen to nitrogen atoms in the alpha-alanine amino acid has been studied by ab initio methods at the HF/6-31G*, HF/6-31 ++ G** and MP2/6-31 ++ G** levels of calculation including the solvent effects by means of self-consistent reaction field theory. An analysis of the results based on the natural bond orbital charges shows that the transition structure presents an imbalance in the sense that the charge shift lags behind the proton transfer and that the bond formation is always in advance with respect to the bond cleavage. All calculation levels show that the barrier height associated with the conformational change on alpha-alanine is larger than the proton transfer process. (C) 1998 Elsevier B.V. B.V. All rights reserved.